How would you solve this by factoring?

3z2 - 48 = 0

I got it down to 3(z - 4)(z + 4) = 0

But I don't know how to get the solution set.... please help?

3z2 - 48 = 0

I got it down to 3(z - 4)(z + 4) = 0

But I don't know how to get the solution set.... please help?

3z2- 48 = 0

3(z2- 16) = 0 {factor 3 out}

3(z + 4)(z - 4) = 0 {z2- 16 is a difference of two squares}

z + 4 = 0 or z - 4 = 0 {set each factor equal to zero}

z = - 4 or z = 4 {solve each equation for z}

- Algebra House

3(z2- 16) = 0 {factor 3 out}

3(z + 4)(z - 4) = 0 {z2- 16 is a difference of two squares}

z + 4 = 0 or z - 4 = 0 {set each factor equal to zero}

z = - 4 or z = 4 {solve each equation for z}

- Algebra House